The Developmental Enhancement of a C4 System With Non-Typical C4 Physiological Characteristics in Salsola ferganica (Kranz Anatomy), an Annual Desert Halophyte - Liu, Yanxia; Maimaitijiang, Tayier; Zhang, Jinghua; Ma, Yali; Lan, Haiyan (Frontiers in Plant Science, 2020)
Variations of photosynthetic structures in different tissues or cells are in coordination with changes in various aspects, e.g. physiology, biochemistry, gene expression, etc. Most C4 plant species undergo developmental enhancement of the photosynthetic system, which may present different modes of changes between anatomy and physiology/biochemistry. In the current study, we investigated a Kranz-type C4 species Salsola ferganica with the progressive development of photosynthetic (PS) structure, performance of PS physiology, induction of PS enzymes, and transcriptional & translational regulation of PS genes: results revealed that S. ferganica presented C3 type anatomy in cotyledons but C4 type in leaves (C3/L4), with the C4 system separation of initial carbon fixation in the palisade mesophyll (M) cells and the following incorporation into triosephosphates and sugars in the bundle sheath (BS) cells, respectively. The BS cells continuously surrounded the vascular bundles and water storage cells in leaf anatomic structure. Compared to the single-cell C4 species Suaeda aralocaspica, S. ferganica exhibited similar developmental enhancement of C4 syndrome temporally and spatially in anatomic structures, enzyme activities and gene expression, which suggests that completion of differentiation of the photosynthetic system is necessary for a C4 assimilation pathway. Besides, S. ferganica also displayed some different characteristics compared to S. aralocaspica in photosynthetic physiology, e.g. a more flexible δ13C value, much lower phosphoenolpyruvate carboxylase (PEPC) activity and an insensitive response to stimuli, etc., which were not typical C4 characteristics. We speculate that this may suggest a different status of these two species in the evolutionary process of the photosynthesis pathway. Our findings will contribute to further understanding of the diversity of photosynthesis systems in Kranz-type C4 species and the Salsola genus.